Modulation of Nerve Injury–induced HDAC4 Cytoplasmic Retention Contributes to Neuropathic Pain in Rats. (July 2015) - Lin, Tzer-Bin; Hsieh, Ming-Chun; Lai, Cheng-Yuan; Cheng, Jen-Kun; Chau, Yat-Pang; Ruan, Ting; Chen, Gin-Den; Peng, Hsien-Yu
Abstract : Background: The histone deacetylases (HDACs) have been implicated in pain hypersensitivity. This study investigated the potential involvement of an HDAC4-related mechanism in the spinal nerve ligation (SNL)-induced nociceptive hypersensitivity. Methods: The left L5 to L6 spinal nerves of 627 adult male Sprague–Dawley rats were surgically ligated. The withdrawal threshold of hind paws and the abundances, cellular location, and interactions of proteins in the dorsal horn were assayed before and after surgery. The 14-3-3β-targeting small-interfering RNA, a serum- and glucocorticoid-inducible kinase 1 (SGK1) antagonist, or an HDAC inhibitor was spinally injected to elucidate the role of 14-3-3β, SGK1, and HDAC4. Results: Without affecting the HDAC4 level, SNL provoked SGK1 phosphorylation (mean ± SEM from 0.24 ± 0.02 to 0.78 ± 0.06 at day 7, n = 6), HDAC4 phosphorylation (from 0.38 ± 0.03 to 0.72 ± 0.06 at day 7, n = 6), 14-3-3β expression (from 0.53 ± 0.09 to 0.88 ± 0.09 at day 7, n = 6), cytoplasmic HDAC4 retention (from 1.18 ± 0.16 to 1.92 ± 0.11 at day 7, n = 6), and HDAC4-14-3-3β coupling (approximately 2.4-fold) in the ipsilateral dorsal horn in association with behavioral allodynia. Knockdown of spinal 14-3-3β expression prevented the SNL-provoked HDAC4 retention (from 1.89 ± 0.15 to 1.32 ± 0.08 at day 7, n = 6), HDAC4-14-3-3β coupling (approximately 0.6-fold above SNL 7D), and behavioral allodynia (from 0.16 ± 0.3 to 6 ± 1.78 at day 7, n = 7), but not SGK1 (from 0.78 ± 0.06 to 0.71 ± 0.04 at day 7, n = 6) or HDAC4 (from 0.75 ± 0.15 to 0.68 ± 0.11 at day 7, n = 6) phosphorylation. Conclusion: Neuropathic pain maintenance involves the spinal SGK1 activation–dependent HDAC4 phosphorylation and its subsequent association with 14-3-3β that promotes cytoplasmic HDAC4 retention in dorsal horn neurons. Abstract : In a rat model of neuropathic pain, histone deacetylases 4 phosphorylation led to its cytoplasmic retention due to phosphorylation-dependent interaction with 14-3-3β. Inhibition of histone deacetylases phosphorylation reduced allodynia and prevented its cytoplasmic translocation, suggesting a novel therapeutic target for neuropathic pain.